Avaliação do alinhamento entre critérios competitivos e práticas de autonomação na indústria eletrônica: um estudo de caso - Silva, Macáliston Gonçalves da (Universidade do Vale do Rio dos Sinos, 2010)
This research aims at proposing and testing a method for the assessment of the alignment between competitive criteria and Autonomation practices, using theoretical and empirical basis. In order to create a heuristic situation and to apply the proposed method, a case study was conducted at a company that manufactures high-tech electronic equipment. The comprehension of the constructs that represent the application of Autonomation is supported by the theoretical review of concepts involving Autonomation, its impact on the production system and the interaction with the competitiveness at the enterprise?s level. The elements that influence each construct in the production process are identified through a focus group. The indicators found were weighed and measured, allowing the identification and quantification of gaps. The results are analyzed and discussed from the viewpoint of Industrial Engineering, proposing a plan of actions and implications for the improvement of the assessed process. This thesis contributes to the construction and development of a model representing the relationships among constructs, competitive criteria, and factors of the application of Autonomation. It is considered that the proposed method approximates the operational approaches to strategic settings, avoiding isolated and inefficient initiatives in manufacturing. Thus, it can be seen as a managerial tool, which can be useful for supporting the achievement of a pre-established manufacturing strategy.
Keywords: Estratégia de produção; Automação (Jidoka); Indústria eletrônica; Manufacturing strategy; Autonomation (Jidoka); Electronics industry; ACCNPQ::Engenharias::Engenharia de Produção